Penguatan Kerjasama Pendidikan, Dakwah dan Kemanusiaan antara Al-Azhar dan Organisasi Islam di Indonesia - Mujamil, Imam; Indriansyah, Teddy; Ishak, Ishak; Subarkah, Milana Abdillah (Masterpiece: Journal of Islamic Studies and Social Sciences, 2024)
This study examines the strengthening of educational, da'wah, and humanitarian cooperation between Al-Azhar and Islamic organizations in Indonesia. This collaboration is realized through various scholarship programs, training, and the dissemination of Wasathiyyah Islam to create a young generation capable of promoting the values of moderation and tolerance. These scholarship programs not only provide broad access to education but also enhance academic quality with direct guidance from experts at Al-Azhar. The study employs a descriptive qualitative method with a case study approach. Data were collected through direct observation, in-depth interviews with relevant parties, and analysis of official documents related to the visit of the Vice Grand Sheikh of Al-Azhar. The findings of this study affirm the strong commitment of both parties to support inclusive Islamic education and da'wah. Al-Azhar actively supports human resource development in Indonesia through sustainable programs. Intensive training programs include teaching effective da'wah methodologies, understanding moderate theology, and developing leadership skills to face contemporary challenges. This cooperation is expected to have a positive impact on improving the quality of Islamic education, strengthening bilateral relations, and promoting the values of moderation and tolerance. With productive collaboration, both parties are optimistic about realizing the vision of creating a morally upright young generation capable of contributing to the global community. Abstrak Penelitian ini mengkaji tentang penguatan kerjasama pendidikan, dakwah, dan kemanusiaan antara Al-Azhar dan organisasi Islam di Indonesia. Kerja sama ini diwujudkan melalui berbagai program beasiswa, pelatihan, dan sosialisasi Islam Wasathiyyah untuk melahirkan generasi muda yang mampu mengedepankan nilai-nilai moderasi dan toleransi. Program beasiswa ini tidak hanya memberikan akses luas terhadap pendidikan tetapi juga meningkatkan kualitas akademik dengan bimbingan langsung dari para ahli di Al-Azhar. Penelitian ini menggunakan metode deskriptif kualitatif dengan pendekatan studi kasus. Pengumpulan data dilakukan melalui observasi langsung, wawancara mendalam dengan pihak-pihak terkait, dan analisis dokumen resmi terkait kunjungan Wakil Syekh Agung Al-Azhar. Temuan penelitian ini menegaskan komitmen kuat kedua belah pihak untuk mendukung pendidikan Islam inklusif dan dakwah. Al-Azhar aktif mendukung pengembangan sumber daya manusia di Indonesia melalui program-program berkelanjutan. Program pelatihan intensif meliputi pengajaran metodologi dakwah yang efektif, pemahaman teologi moderat, dan pengembangan keterampilan kepemimpinan untuk menghadapi tantangan kontemporer. Kerja sama ini diharapkan dapat memberikan dampak positif terhadap peningkatan kualitas pendidikan Islam, mempererat hubungan bilateral, serta mengedepankan nilai-nilai moderasi dan toleransi. Dengan kerja sama yang produktif, kedua belah pihak optimis dapat mewujudkan visi mewujudkan generasi muda yang bermoral dan mampu berkontribusi pada masyarakat global.